2012
DOI: 10.1103/physreva.86.013804
|View full text |Cite
|
Sign up to set email alerts
|

Diameter-bandwidth product limitation of isolated-object cloaking

Abstract: We show that cloaking of isolated objects is subject to a diameter-bandwidth product limitation: as the size of the object increases, the bandwidth of good (small cross-section) cloaking decreases inversely with the diameter, as a consequence of causality constraints even for perfect fabrication and materials with negligible absorption. This generalizes a previous result that perfect cloaking of isolated objects over a nonzero bandwidth violates causality. Furthermore, we demonstrate broader causality-based sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 59 publications
1
32
0
Order By: Relevance
“…In recent work [42] we have bounded the scattering properties of any dissipative medium excited by a known, externally generated incident field. The bounds arise from the functional dependencies of power expressions with respect to induced currents: absorption is a quadratic functional, whereas extinction (absorption+scattering), given by the optical theorem [44][45][46][47], is only a linear functional. Energy conservation requires that extinction be greater than absorption, which imposes a bound on the magnitude of the excited currents.…”
mentioning
confidence: 99%
“…In recent work [42] we have bounded the scattering properties of any dissipative medium excited by a known, externally generated incident field. The bounds arise from the functional dependencies of power expressions with respect to induced currents: absorption is a quadratic functional, whereas extinction (absorption+scattering), given by the optical theorem [44][45][46][47], is only a linear functional. Energy conservation requires that extinction be greater than absorption, which imposes a bound on the magnitude of the excited currents.…”
mentioning
confidence: 99%
“…which is similar to the form of the optical theorem given in [34,23,37], and W = 2k 0 π Im[p a P s ∞ (k 0 /k 0 )]/(ωρ 0 ), (7.8) which is the well-known form of the optical theorem [58,15] for acoustic scattering.…”
Section: A Minimization Variational Principle For Acoustic Scatteringmentioning
confidence: 63%
“…Scattering coefficient study in different cylindrical wave orders have been shown with simplified material properties [11,12]. Until now, discussions on the bandwidth and practical limitations of electromagnetic cloak present in the published results [13][14][15][16][17][18] are few in number.…”
Section: Introductionmentioning
confidence: 96%